Acute Flaccid Myelitis: Something Old and Something New - David M. Morens (American Society for Microbiology, 2019)
ABSTRACT Since 2014, acute flaccid myelitis (AFM), a long-recognized condition associated with polioviruses, nonpolio enteroviruses, and various other viral and nonviral causes, has been reemerging globally in epidemic form. This unanticipated reemergence is ironic, given that polioviruses, once the major causes of AFM, are now at the very threshold of global eradication and cannot therefore explain any aspect of AFM reemergence. Instead, the new AFM epidemic has been temporally associated with reemergences of nonpolio enteroviruses such as EV-D68, until recently thought to be an obscure virus of extremely low endemicity. This perspective reviews the enigmatic epidemiologic, virologic, and diagnostic aspects of epidemic AFM reemergence; examines current options for clinical management; discusses future research needs; and suggests that the AFM epidemic offers important clues to mechanisms of viral disease emergence.